UNLOCKING HIDDEN POTENTIAL OF SHALLOW RESERVOIR AT 1955-2342 mSS, IN RUHOUL FIELD - Abda Anwaratutthifal; Lestari Lestari; Reno Pratiwi (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2019)
As a human, live in the ever-changing environment, with the abundant amount of human movement, increasing population, and advancing technology, consumpting high energy is inevitable. Indonesia has been working to obtain better energy to fuel the world. As the multinational energy company, Pertamina Hulu Mahakam, located in East Kalimantan, operate world wide to extract oil and gas from the reservoir in Mahakam Delta, which already used high technology and qualified human resource to support the safe, efficient, and effective production process.The petroleum system models, the contribution of marine shales to the generation of liquid and gaseous hydrocarbons in the Mahakam was considered negligible. The production of the oil fields has started quite early, however the major development phase of gas accumulation started within the last decade, with increasing activity since.Ruhoul is an offshore gas field belongs to Pertamina Hulu Mahakam that located in Mahakam Delta, East Kalimantan, Indonesia. It covers an area of 350 km2 and has a gross thickness of the payzone over 2000 m. Structural architecture of Ruhoul field is multilayered un-faulted anticline. Stratighraphycally, Ruhoul reservoirs are divided into two intervals which are Ruhoul Main Zone and Ruhoul Shallow. This study is only focused in Shallow zone area, they are Sh-8a, Sh-8c, and Sh-8d, as it is considered as remaining prospective area for Ruhoul field. For more specific, Sh-8a was produced by wells RJ-16A-M and RJ-2G-M.T3, Sh-8c was produced by well RJ-2G-M.T3, and Sh-8d was produced by well RJ-2G-M-T3.Over time, the gas production in Ruhoul Field keep decreasing, therefore hidden gas production potential needs to be re-evaluated. The evaluation can be done by doing the dynamic synthesis analysis based on completion type used, production history, and well correlation.The main objective of this study is to evaluate hydrocarbon potential in Ruhoul Shallow specific area. Several approaches will be used to assess Ruhoul Shallow zone prospect such an updated database, zone change inventory, and well correlation based on netpay map by layer with software Geolog 7.2.Perform Dynamic Synthesis Analysis and P/Z Straight Line Material Balance Calculation are chosen as the methodology to assess the prospect zone of this field. The results of this process are candidates to be the re-opening zone, the value of GIIP, EUR, RR, RF, also the drive mechanism applied to each layer. Not only that, the results also obtained the Plateau rate stage curve in each layer.The results showed two categories of re-opening candidates, P/Z methodology to calculate the value of GIIP and RF, and Plateau stage in each layer. Along with this study, the only well that suit to be the candidate for re-opening zone was only RJ-2G-M.T3 in Sh-8a, while the other layers and wells were not suit to be the candidate for re-opening zone. From the P/Z Straight Line calculation, the GIIP for the candidate (Sh-8a produced by RJ-2G-M.T3) is 1.15 BSCF, with 1.02 BSCF Gp max, and 89% RF, and has depletion drive as its drive mechanism. Based on Plateau stage with 4 MMSCFD as the plateau rate, the decline in RJ-2G-M.T3 (Sh-8a) started on July 2015.